SME marketing: efficiency in practice. Issue 3 (2nd September 2018) - Gilmore, Audrey; Carson, David
ABSTRACT: Much has been written about SME owner-manager decision making and SME marketing efficiency. SME marketing theories have been drawn from the marketing, management and entrepreneurship literatures. These have provided the foundation for investigative empirical work focusing on how SME owner-managers actually do business. This paper reviews the relevant literature and offers some insights based on experience of working with SMEs at different stages of their development. Then two SME case examples are used to illustrate how SME owner-managers develop specific business activities within very competitive markets by focusing on SME business efficiency in practice. The case findings are considered in the context of current business practice and leadership thinking.